State, Religion, and Modernity: A Critical Analysis of the Relationship Between Political Islam and the State in the Context of Reform - Siful, Siful; Hasir, Hasir; Iqbal, Muhammad (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study examines the dynamics of Islamic politics in the process of forming a modern state, focusing on the relationship between religion and the state in the context of political modernization during the reform era. The main issue explored is how Islamic politics adapts to and interacts with the principles of a modern state and the impact of religion-state integration on democratization in post-reform Indonesia. This study aims to understand the role of Islamic politics in forming a modern state, identify the challenges and opportunities in integrating religion and the state, and assess the extent to which Islamic politics can contribute to stability and the sustainability of democracy. This research employs a qualitative method with a descriptive approach. Data is collected through literature reviews and document analysis related to political policies, legal regulations, and the development of Islamic politics in Indonesia. The findings indicate that Islamic politics has undergone significant changes in facing the challenges of the modern state. The integration between religion and the state remains a topic of debate between groups advocating Islam as the foundation of the state and those supporting secularism. However, compromises between Islamic values and democratic principles can be observed in legal regulations and government policies in the post-reform era. In conclusion, Islamic politics is crucial in forming a modern state. However, the integration of religion and the state must be balanced to avoid hindering the democratization process. Therefore, inclusive policies are needed to ensure that the role of Islam in politics remains in harmony with democratic principles and the diversity of Indonesian society. [Penelitian ini mengkaji dinamika politik Islam dalam proses pembentukan negara modern dengan fokus pada hubungan antara agama dan negara dalam konteks modernisasi politik pada era reformasi. Permasalahan utama yang diteliti adalah bagaimana politik Islam menyesuaikan diri dan berinteraksi dengan prinsip negara modern, serta dampak integrasi agama dan negara terhadap demokratisasi di Indonesia pasca-reformasi. Tujuan penelitian ini adalah untuk memahami peran politik Islam dalam pembentukan negara modern, mengidentifikasi tantangan dan peluang dalam integrasi agama dan negara, serta menilai sejauh mana politik Islam dapat mendukung stabilitas dan kelangsungan demokrasi. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui studi pustaka dan analisis dokumen yang berkaitan dengan kebijakan politik, regulasi hukum, serta perkembangan politik Islam di Indonesia. Hasil penelitian menunjukkan bahwa politik Islam mengalami perubahan yang cukup signifikan dalam menghadapi tantangan negara modern. Integrasi antara agama dan negara tetap menjadi perdebatan antara kelompok yang menginginkan Islam sebagai dasar negara dan kelompok yang mendorong sekularisme. Namun, dalam praktiknya, kompromi antara nilai-nilai Islam dan prinsip demokrasi dapat ditemukan dalam regulasi hukum serta kebijakan pemerintahan pasca-reformasi. Sebagai kesimpulan, politik Islam memiliki peran krusial dalam pembentukan negara modern, tetapi integrasi agama dan negara harus dikelola dengan seimbang agar tidak menghambat proses demokratisasi. Oleh karena itu, diperlukan kebijakan yang inklusif agar peran Islam dalam politik tetap selaras dengan prinsip demokrasi dan keberagaman di Indonesia].